Primary PCI for STEMI in Patients with Chronic Total Occlusions - Ali, Nasir; Hameed Ullah,; Khan, Muhammad Niaz; Abdul Waris,; Abid Ullah,; Nazeef Ullah, (Indus Journal of Bioscience Research, 2025)
Objective: To evaluate the impact of chronic total occlusions (CTOs) on procedural and clinical outcomes in ST-segment elevation myocardial infarction (STEMI) patients undergoing primary PCI at a tertiary care hospital. Methodology: A retrospective cohort study was carried out at Hayatabad Medical Complex, Peshawar, during a duration of 12 months in which 400 patients were enrolled and divided into two groups, STEMI with CTOs (Group A, n=100) and STEMI without CTOs (Group B, n=300). Baseline characteristics, procedural outcomes, and clinical events were examined. Outcomes were compared with statistical tests (chi-square and t-tests); p-values <0.05 were considered significant. Results: The average age in group A is 62.5 ± 10.4 years and 59.8 ± 9.9 years in group B (p=0.07). Time to PCI was significantly longer in Group A compared with Group B (7.2 ± 2.5 hours vs 5.4 ± 1.9 hours, p<0.01). PCI success was lower in Group A (85%) than in Group B (95%, p=0.02) In-hospital MACE was seen in 15% of Group A compared to 10% of Group B (p=0.15). The follow-up MACCE rates were higher in group A (20%) compared to group B (12%, p=0.09), with the corresponding mortality rates of 12% and 7%, respectively (p=0.11). Conclusion: STEMI patients with CTOs face longer procedural times, lower success rates, and higher adverse event rates, emphasizing the need for advanced interventional strategies and tailored management protocols to improve outcomes.